Efektifitas Dan Kredibilitas Para Pengguna Fintech Dalam Permasalahan Transfer Rekening Antar Bank - Rachmah, Dea Nur; Affandi, Imanudin (Peneliti.net, 2024)
Public anxiety about the admin fees given by banks when transferring between banks has resulted in many fintech companies wanting to take part in making these transactions. Assisted by the advancement of the world of Interconnection-Networking (ICT), nowadays it is giving birth to ideas and products that can help and facilitate users in various ways. Including conducting financial transactions. Where in the past, when you wanted to make a transaction, every person had to go to a related outlet or bank or even an ATM at once, but with the advancement of ICT now it can be done easily. The transfer fee given by the bank is up to Rp. 6,500, where these companies can reduce it far from the admin price that the bank provides. So great is the influence of the ICT world in terms of banking that it has become a necessity for the technology itself. The high number of internet service users in Indonesia also has an impact on the rapid growth of Fintech companies, the rapid growth of fintech companies because they can offer a variety of financial services that help people to make the economy more effective.